2020
DOI: 10.1016/j.devcel.2020.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Heterogeneity and Lineage Restriction during Mouse Digit Tip Regeneration at Single-Cell Resolution

Abstract: Highlights d Unbiased atlas of cell types throughout mouse digit tip regeneration d The early blastema contains all broad cell lineages found in the unamputated digit tip d Fibroblasts are the most abundant and heterogeneous population d Dynamics of distinct fibroblast populations reveal regeneration-specific markers

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 70 publications
(134 reference statements)
5
93
0
Order By: Relevance
“…500 μl 2% SDS in 50 mM ammonium bicarbonate in MS-grade water was added to the bead pellet, and the mixture was transferred into a low-protein-binding tube. Beads were then washed ( Goldman et al, 2017 ) twice with 500 μl 0.5% SDS in 50 mM ammonium bicarbonate ( Hoang et al, 2020 ), twice with 1% Triton X-100/1% deoxycholate/25 mM LiCl in 50 mM ammonium bicarbonate ( Johnson et al, 2020 ), twice with 0.5 M NaCl in 50 mM ammonium bicarbonate, and two times with 50 mM ammonium bicarbonate solution. For each wash step, 500 μl wash solution was used and samples were rocked for 10 min at RT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…500 μl 2% SDS in 50 mM ammonium bicarbonate in MS-grade water was added to the bead pellet, and the mixture was transferred into a low-protein-binding tube. Beads were then washed ( Goldman et al, 2017 ) twice with 500 μl 0.5% SDS in 50 mM ammonium bicarbonate ( Hoang et al, 2020 ), twice with 1% Triton X-100/1% deoxycholate/25 mM LiCl in 50 mM ammonium bicarbonate ( Johnson et al, 2020 ), twice with 0.5 M NaCl in 50 mM ammonium bicarbonate, and two times with 50 mM ammonium bicarbonate solution. For each wash step, 500 μl wash solution was used and samples were rocked for 10 min at RT.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding how and why tissue regeneration occurs is a central objective of developmental biology. Genome-wide transcriptome or chromatin profiling experiments using RNA-seq, scRNA-seq, ATAC-seq, or ChIP-seq approaches have helped to identify novel factors, mechanisms, and concepts that have informed our understanding of regeneration in many tissues, injury contexts, and species ( Goldman et al, 2017 ; Hoang et al, 2020 ; Johnson et al, 2020 ). Although key for detecting and inferring changes in gene transcription, chromatin organization, or DNA–protein associations, these strategies are limited in their abilities to identify protein and signaling complexes that carry out changes at the cell and tissue level.…”
Section: Introductionmentioning
confidence: 99%
“…The gene aspr encodes a secreted protein with multiple EGF-repeats important for regeneration (Harris et al ., 2020). Pvf1 binds to its receptor Pvr and the resulting signaling is known to contribute to wound healing (Wu et al ., 2009), and homologs are involved in regeneration in other systems (Currie et al ., 2016; Johnson et al ., 2020). We determined that Pvf1, upd3 , and Ilp8 were all expressed at the center of the blastema (Figure 1H, I; supplemental fig.…”
Section: Figurementioning
confidence: 99%
“…The same transplantation, performed in the proximally amputated, therefore non-regenerative digits, had no similar effect on the phenotype of the introduced cells, confirming the role of blastema in altering the inherent cells’ transcriptional state [ 50 ]. Cell population in the early blastema (11–17 days post-amputation) of the regenerating digit tip was recently analyzed via scRNA-seq by Johnson et al [ 64 ], who identified the very same broad cell types in the intact unamputated digit tip. The most abundant and heterogeneous population within the blastema were fibroblasts, which were also observed to be enriched in several regeneration-specific markers, including a novel Mest gene [ 64 ].…”
Section: Digit Regenerationmentioning
confidence: 99%
“…Cell population in the early blastema (11–17 days post-amputation) of the regenerating digit tip was recently analyzed via scRNA-seq by Johnson et al [ 64 ], who identified the very same broad cell types in the intact unamputated digit tip. The most abundant and heterogeneous population within the blastema were fibroblasts, which were also observed to be enriched in several regeneration-specific markers, including a novel Mest gene [ 64 ]. The Mest gene expression was previously identified in mesenchymal tissues of the developing embryo [ 65 ].…”
Section: Digit Regenerationmentioning
confidence: 99%